1999
DOI: 10.1016/s0921-4526(99)00568-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of defect formation and electronic transport in microcrystalline silicon deposited by hot-wire CVD

Abstract: Abstract:We have investigated doped and undoped layers of microcrystalline silicon prepared by hot wire chemical vapour deposition optically, electrically and by means of transmission electron microscopy. Beside needlelike crystals grown perpendicular to the substrate's surface all of the layers contained a noncrystalline phase with a volume fraction between 4% and 25%. A high oxygen content of several per cent in the porous phase was detected by electron energy loss spectrometry. Deep level transient spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Frequency dependent capacitance−voltage and conductance−voltage measurements confirmed that the DLTS measurements provided information on defects in the crystalline phase [3]. DLTS measurements on undoped µc−Si/ZnO rectifying Schottky diode structures revealed three easily resolvable donors with activation energies of 0.027eV, 0.185eV potentially induced by interstitial Cu + and 0.336eV which may be attributed to tungsten from the hot filament.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Frequency dependent capacitance−voltage and conductance−voltage measurements confirmed that the DLTS measurements provided information on defects in the crystalline phase [3]. DLTS measurements on undoped µc−Si/ZnO rectifying Schottky diode structures revealed three easily resolvable donors with activation energies of 0.027eV, 0.185eV potentially induced by interstitial Cu + and 0.336eV which may be attributed to tungsten from the hot filament.…”
Section: Resultssupporting
confidence: 52%
“…One acceptor with an activation energy of 0.104eV could be resolved. DLTS on pin diodes revealed three more shallow donor levels with activation energies lower than 0.140eV attributed to oxygen [3]. Despite the presence of a noncrystalline phase usually causing defect induced band tails as observed by optical absorption measurements distinct defect levels could be measured by DLTS typical for crystalline material.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…At the same time, the doping level may influence the degree of the structural disorder, film crystallinity, and defect density distribution. Various carrier transport mechanisms have been reported for a-Si: H, 9-11 c-Si: H, 12,13 and nc-C:H films. 14 In this paper, we investigated the electric transport of p-nc-Si− SiC: H alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Improved understanding of these mechanisms may afford a better control of the deposition process and yield a higher performance devices. Furthermore, little has been reported on the structural and morphological properties of such films 1,2,3 .…”
mentioning
confidence: 99%